DEVELOPMENT OF ARTIFICIAL INTELLIGENCE (AI) SYSTEMS FOR BUSINESS SYSTEM OPTIMIZATION - Muhammad Yazid Syafiq; Indah Nur Afhiva; Yaga Taruma Tarigan; Syafina Almaira Nazmi Aswin Nasution; Fadly Ardian Syahputra (Bulletin of Engineering Science, Technology and Industry, 2025)
The advancement of artificial intelligence (AI) technology has brought major changes in various fields including business. This study aims to analyze the potential for developing AI systems to optimize business processes in Indonesia using a literature review approach. This study highlights trends, benefits, and challenges in AI implementation and shows that AI can improve efficiency, productivity, and innovation. Although the application of AI in Indonesia is still in its early stages, its potential is very large, especially in logistics and e-commerce. However, challenges such as limited access to technology and low digital literacy are still the biggest obstacles. This study uses a systematic literature review (SLR) technique to explore the application of technologies such as machine learning (ML), natural language processing (NLP), and robotic process automation (RPA) to improve operational efficiency. This study shows that with the right implementation strategy, AI can help Indonesian companies compete in the global market and accelerate their digital transformation.